(2R, 3R)Dihydromyricetin inhibits osteoclastogenesis and bone loss through scavenging LPS‐induced oxidative stress and NF‐κB and MAPKs pathways activating. Issue 11 (4th August 2018) - Zhang, Xuejun; Li, Xin; Fang, Jianguo; Hou, Xiaolong; Fang, Huang; Guo, Fengjing; Li, Feng; Chen, Anmin; Huang, Shilong
Abstract: Osteolysis is a serious complication of several chronic inflammatory diseases and is closely associated with a local chronic inflammatory reaction with a variety of causes. However, similarities exist in the mechanisms of their pathological processes. Inflammatory factors and oxidative stress–induced nuclear factor κB (NF‐κB) and mitogen‐activated protein kinases (MAPKs) signaling pathways play a center role in bone erosion. Dihydromyricetin (DMY) is a natural compound with anti‐inflammatory and antioxidative effect, which are commonly used in chronic pharyngitis and alcohol use disorders. In the current study, we identified that DMY attenuated lipopolysaccharide (LPS)–induced oxidative stress through inhibiting the production of reactive oxygen species (ROS) and nitric oxide (NO), downregulated COX‐2 and iNOS, and promoted the activity of the antioxidative system by activating superoxide dismutase (SOD) and Nrf2/HO‐1 pathway. To further investigate the underlying mechanism, we found that DMY inhibits osteoclast (OC) differentiation and bone resorption activity through blocking the RANKL‐induced activation of the NF‐κB and MAPKs signaling pathways and then downregulated c‐Fos and NFATc1, which is essential for OC differentiation. Furthermore, DMY inhibited LPS‐induced osteolysis in vivo. Collectively, these results indicate that DMY might be a promising prophylactic antiosteoclastic/resorptive agent in preventing or treating bone lysis diseases. Abstract : Dihydromyricetin (DMY) inhibits osteoclast differentiation and bone resorption activity through blocking the RANKL‐induced activation of the NF‐κB and MAPKs signaling pathways and then downregulated c‐Fos and NFATc1, DMY also attenuated lipopolysaccharide (LPS)‐induced oxidative stress through inhibiting the production of ROS and NO and downregulating COX‐2 and iNOS, and promoted the activity of the antioxidative system by activating SOD and the Nrf2/HO‐1 pathway, and inhibited LPS‐induced osteolysis in vivo.